2017
DOI: 10.1111/jace.15095
|View full text |Cite
|
Sign up to set email alerts
|

Equiaxed β–Si3N4 ceramics prepared by rapid reaction‐bonding and post‐sintering using TiO2–Y2O3–Al2O3 additives

Abstract: Sintered reaction‐bonded Si3N4 ceramics with equiaxed microstructure were prepared with TiO2–Y2O3–Al2O3 additions by rapid nitridation at 1400°C for 2 hours and subsequent post‐sintering at 1850°C for 2 hours under N2 pressure of 3 MPa. It was found that α–Si3N4, β–Si3N4, Si2N2O, and TiN phases were formed by rapid nitridation of Si powders with single TiO2 additives. However, the combination of TiO2 and Y2O3–Al2O3 additives led to the formation of 100% β–Si3N4 phase from the nitridation of Si powders at such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This is the opposite of what is found in the literature. Wu et al [33] investigated the effect of TiO 2 and TiO 2 /ZrO 2 /Y 2 O 3 addition to Si 3 N 4 on the formation of the Si 2 N 2 O phase. They showed that Si 2 N 2 O does not form in ceramics with oxide sintering activators.…”
Section: Resultsmentioning
confidence: 99%
“…This is the opposite of what is found in the literature. Wu et al [33] investigated the effect of TiO 2 and TiO 2 /ZrO 2 /Y 2 O 3 addition to Si 3 N 4 on the formation of the Si 2 N 2 O phase. They showed that Si 2 N 2 O does not form in ceramics with oxide sintering activators.…”
Section: Resultsmentioning
confidence: 99%